Polled Hereford and Simmental milk production - Schalles, R.R.; Kimbrough, S.; Zoellner, K.O.; Simms, D.D. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The weigh-suckle-weigh method was used to measure milk consumption by 265 calves from 159 Polled Hereford and Simmental cows over 3 years. Calves nursing Polled Hereford cows consumed an average of 11.2 lbs of milk per day, with a peak of 15lbs at 50 days post• calving. calves nursing Simmental cows consumed an average of 16.8 lbs of milk per day, with a peak of 20 lbs at 58 days after calving. All increase of 1lb in daily milk consumption produced approximately 20 lbs increase in weaning weight.
Keywords: Beef; Hereford; Simmental; Milk production